2007
DOI: 10.4141/p06-035
|View full text |Cite
|
Sign up to set email alerts
|

Row spacing and irrigation effects on water consumption of winter wheat in Taian, China

Abstract: . 2007. Row spacing and irrigation effects on water consumption of winter wheat in Taian, China. Can. J. Plant Sci. 87: 471-477. Management practices can have a major impact on the successful production of winter cereals. A field experiment was conducted with winter wheat (Triticum aestivum) to compare the effects of two row spacing planting patterns (row width set at 30 cm, 30; or row widths set at a narrow row of 20 cm and a wide row of 40 cm, 20 + 40) and four irrigation schedules (no irrigation, T0; irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Several effective irrigation patterns have been developed, such as limited irrigation, regulation of deficit irrigation, and surge flow irrigation (Fabeiro et al, 2002;Horst et al, 2007;Kang et al, 2000). Deficit irrigation is an optimization strategy that focuses on reducing water use and increasing WUE worldwide (Li et al, 2004;Soundharajan and Sudheer, 2009;Zhou et al, 2007). Evapotranspiration decreases with decrease of irrigation and can significantly contribute to an increase in WUE and grain yield of crops in deficit-irrigation regimes (Jiang et al, 2012;Zhang et al, 1998Zhang et al, , 2008.…”
mentioning
confidence: 99%
“…Several effective irrigation patterns have been developed, such as limited irrigation, regulation of deficit irrigation, and surge flow irrigation (Fabeiro et al, 2002;Horst et al, 2007;Kang et al, 2000). Deficit irrigation is an optimization strategy that focuses on reducing water use and increasing WUE worldwide (Li et al, 2004;Soundharajan and Sudheer, 2009;Zhou et al, 2007). Evapotranspiration decreases with decrease of irrigation and can significantly contribute to an increase in WUE and grain yield of crops in deficit-irrigation regimes (Jiang et al, 2012;Zhang et al, 1998Zhang et al, , 2008.…”
mentioning
confidence: 99%
“…In our previous work, we demonstrated that the seeding-jointing stage was a critical period for amount of population (Zhou et al 2007). RS14 exhibited the highest amount of population and RS49 had the lowest; in effect, the ET of RS14 was significantly higher than those of other treatments (P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…In most years, from October to May, in the winter wheat growing season, rainfall is about 200 mm (20-30% of annual precipitation). The water requirement of winter wheat (~ 400-500 mm) in spring exceeds precipitation; monthly rainfall data shows that water supply from rainfall is inadequate to match crop ontogeny (Zhou et al 2007).…”
mentioning
confidence: 99%
“…However, the increasing water scarcity and the competition from other sectors have put agricultural water use under great pressure (Yang & Zehnder, 2001;Liu et al, 2007b;Guler, 2010). Irrigation water is becoming an increasingly scarce resource in many areas, as a consequence an appropriate choice of irrigation scheduling is necessary to maximize yield and profit (Zhou et al, 2007(Zhou et al, , 2011. It is known that shoratge of water restricts crop productivity and the purpose of irrigation is to minimise crop water stress and to achieve maximum yield (Ghane et al, 2009;Wang et al, 2009;Ghassemi-Golezani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%